KINERJA APARATUR SIPIL NEGARA DALAM PELAYANAN PENDAFTARAN TANAH DI KANTOR PERTANAHAN KOTA PALU PROVINSI SULAWESI TENGAH - Siswoyo, Siswoyo; Pasinringi, Andi; Susanti, Ani (Katalogis, 2019)
As a public organization that provides services to the community, the Palu City Land Office through its apparatus is required to always improve its performance in providing its services to the community, because the demands of democratization and recognition of human rights will give rise to strong demands on the performance of services provided by agencies. the government through its apparatus to the public. The purpose of this study was to determine the performance of the State Civil Apparatus in land registration services at the Land Office of Palu City, Central Sulawesi Province. This type of research is descriptive, with the number of informants involved as many as 6 informants, which for determining the informants using Purposive Sampling techniques. In addition, in the data collection technique in this study through observation, interviews, and documentation. With the method of data analysis with three steps, namely data collection, data reduction, data presentation, and draw conclusions. From the results of the research, it is known that the performance of the State Civil Apparatus in the land registration service at the Palu City Land Office in Central Sulawesi Province is considered to be running poorly, this is due to the existence of several problems found by researchers regarding the performance of apparatus in the agency in the land registration service in The Palu City Land Office, while these problems are aspects of quantity, quality, and timeliness.